The Regulation of Hateful and Hurtful Speech: Liberalism’s Uncomfortable Predicament - Maclure, Jocelyn (McGill Law Journal / Revue de droit de McGill, 2017)
The regulation of speech is a highly sensitive and always evolving ethical, political, and legal issue. On the one hand, hateful and hurtful speech is on the rise, especially, but not exclusively, with regard to the relationship between Islam and the West. We can also think of the radicalization of discourse brought about by the interactive phase of the Internet. On the other hand, demands for the suppression of certain forms of speech proliferate. After reviewing the argument for freedom of expression, I argue that while the notion of harm defended by Millian liberals is too narrow, an “offence principle” is too broad. After defending hate speech laws, I concede that such laws need to target only the speech acts that express the most severe forms of aversion and denigration toward the members of a specific group. I then reflect on the status of “hurtful speech”, which I see as including the performative utterances that stop short of being hateful but nonetheless erode, through their illocutionary force and perlocutionary effects, the social standing and bases for self-respect of those who are targeted. I conclude that the free speech debate reveals a limit of liberal political morality and leaves liberal normative theorists with an uncomfortable predicament, as they have to rely more on the complementary role of pro-social personal dispositions and civic virtues than they generally wish to.